Types of Interjection (A Descriptive Analysis in Dragon Ball Super English Comic Book) - Willyana Ramlan; Yana Putra Triana; Ferany Shaily Maulida (Jurnal Bahasa Inggris Terapan, 2019)
The aims of the study are to describe the types and function of the interjection contained in the comic "Dragon Ball Super Vol.04" by Akira Toriyama. The subject of this research is Dragon Ball Super comic. The object of this research is all the words, phrases and sentences which are interjection in the comic Dragon Ball Super. This study used descriptive qualitative method. The result shows 7 types of interjection contained: Interjection of confused, interjection of approval, interjection of sadness, interjection of anger, interjection of happiness, interjection of attention, and interjection of disgust.